Renewable energy generation in developing countries : influence factors and enablers - Banda, Sylvia (My University, 2021)
Since 2008, South Africa has been experiencing significant bottlenecks in its energy supply. The transition to renewable energy is no longer just an option but a necessity. In demonstrating the commitment to the Kyoto Protocol, which requires a reduction in greenhouse gases and is a response to the electricity crisis, various mechanisms have been applied to stimulate renewable energy production. This study examines the effect of the influencing factors and enablers on renewable energy generation in selected developing countries. To this end, the study investigated if the amount invested in renewable energy, economic, governance, environmental and social factors have an impact on renewable energy output produced in the selected emerging economies. Secondary data which comprised of the renewable energy output, investment and proxy data for the other factors being tested was used in the investigation. A quantitative research design was used, and panel data for the periods 2000-2016 was analysed. Results of the study revealed that the renewable energy generation is impacted diversely by the elements tested. A positive causal link was found between the dollar amount invested and the production of renewable energy. Additionally, the study found that governance, economic, environmental, and social factors can influence renewable energy output favourably or unfavourably. Results of the study suggest that policymakers should consider the effect of these variables when formulating policies to accelerate the transition to a sustainable energy supply system. Furthermore, the results provide possible solutions for budgetary constraints which have limited the transformation of the energy industries in the selected developing countries. Potential to investigate this study further on a country by country basis as data becomes available exists. Additionally, mixed methods may be applied to explore a qualitative element in the study. Keywords: Renewable Energy, Non-renewable energy, Green energy
Thesis (M. Com. (Accounting)) -- University of Limpopo, 2021
Keywords: Renewable energy; Non-renewable energy; Green energy; Renewable energy sources; Power resources -- Study and teaching; Clean energy